A Novel Nonsense MMP21 Variant Causes Dextrocardia and Congenital Heart Disease in a Han Chinese Patient - Yuan, Zhuang-Zhuang; Fan, Liang-Liang; Jiang, Zi-Chen; Yang, Yi-Feng; Tan, Zhi-Ping (Frontiers in Cardiovascular Medicine, 2020)
The position and morphology of human internal organs are asymmetrically distributed along the left–right axis. Aberrant left–right patterning in the developing embryo can lead to a series of congenital laterality defects, such as dextrocardia and heterotaxy syndrome. Laterality defects are a genetic condition; however, pathogenic genetic lesions are found in only one-fifth of patients. In this study, whole-exome sequencing was conducted for 78 patients with laterality defects. We identified a novel stopgain variant in MMP21 (c.G496T; p.G166*) in a Chinese patient with mirror-image dextrocardia. This variant caused a truncated MMP21 mRNA containing only the signal peptide and propeptide, while the coding sequence of matrix metalloproteinase-21 was almost entirely absent. To the best of our knowledge, this novel variant is the first homozygous stopgain variant identified in dextrocardia patients, and the first MMP21 variant found in East Asia. Our findings expand the spectrum of MMP21 variants and provide support for the critical role of MMP21 during left–right patterning in the Han Chinese population.